THE KNOWLEDGE OF VOCABULARY LEARNING STRATEGIES PRACTICE FOR ENGLISH AS A SECOND LANGUAGE LEARNERS - Gumartifa, Asti; Saputri, Kurnia; Yuliani, Sri (Universitas Muhammadiyah Palembang, 2020)
Vocabulary is the first step that must be memorize by learner in speaking English as a foreign language. There are two kinds of vocabulary learning strategies which are breadth vocabulary (recognition) and depth vocabulary (recall). In enhancing L2 vocabulary knowledge students need the awareness of learning strategies used. The active students use learning strategies can increase language skills, self confidence and learning motivation in learning activity process. Learning strategies instruct students to learn independently, responsibly, and actively. Thus, students tend to be more confident and motivated when applied learning strategies in the daily learning process. Besides, teacher ought to teach and motivate students to apply students’ some learning strategies accordingly. Finally after implementing learning strategies, students and teachers need to evaluate the progress students’ vocabulary regularly.